STRATEGI KETAHANAN EKONOMI KELUARGA MISKIN PENERIMA DANA BANTUAN SOSIAL DI KELURAHAN TANAH TINGGI JAKARTA PUSAT - Amalia, Lutfi; Samputra, Palupi Lindiasari (Puslitbangkesos Kementerian Sosial RI, 2020)
This study aims to examine the influence of housing, per capita income, education funding, family security, assets and liabilities to the chances of poor families having strong economic resilience. The research method with the quantitative method uses a questionnaire as an instrument of data collection, with a logistic regression analysis tool. Data consists of 100 samples of poor households in the Tanah Tinggi Village area. The results of the study show that there is an influence of residence, per capita income and education funding on the opportunities of poor families that have strong economic resilience. While assets and liabilities and family guarantees do not have a strong influence on the economic resilience of poor families. Per capita income and education funding have the highest contribution to the chances of poor families having strong economic resilience, each at 42,823 times and 9,278 times. The strategy of saving periodically, increasing income, optimizing and reducing quality of life and increasing sources of income can help strengthen the economic resilience of poor families.